Psychosocial Challenges as Predictors of Transactional Sex Among Undergraduates in Ondo State, Nigeria - Michael, Ifeoluwa Blessing; Ilori, Oyedotun Dolapo; Akerele, Patrick O. (Buletin Konseling Inovatif, 2025)
The study investigated the psychosocial challenges predictive towards engaging in transactional sex among undergraduates within Ondo State, with the moderating role of demographic variables weighed heavily. Employing a descriptive survey design, data were gathered from 404 undergraduates by means of a validated questionnaire (reliability = 0.86) randomly sampled from two public and two private universities. Amongst the findings from descriptive statistics and multiple regression analyses were that peer pressure, financial instability, family dysfunction, and emotional health challenges had significant correlations with involvement in transactional sex while jointly explaining 46.6% of the variance. Financial instability was the strongest predictor, followed by peer pressure, family dysfunction, and emotional health challenges. The moderated multiple regression also found gender, age, academic level, and institution type to be significantly moderating these relationships. Psychosocial challenges affected female students, younger undergraduates, and those at the lower academic levels more, and these associations were weaker for private university students because of more controlled environments and better student welfare systems in place. These factors confirm earlier studies on how socio-economic, cultural, and emotional factors come into play in determining sexual choices for young adults. It can be concluded that transactional sexual practices among undergraduates is a multi-dimensional problem originating from intersecting vulnerabilities and modulated by demographic variables. These findings, therefore, vouch for gender-sensitive programs, early-stage student mentorship, financial empowerment, and institution-based policy reforms in a bid to reduce vulnerability. These results, therefore, have major counseling, policy, and targeted student support program implications for Nigerian higher education.